Differences in Sampling Site on Postmortem Cerebrospinal Fluid Biochemistry: A Preliminary Study. (December 2018) - Garland, Jack; Philcox, Winston; Kesha, Kilak; Morrow, Paul; Lam, Leo; Spark, Amy; Palmiere, Cristian; Elstub, Hannah; Cala, Allan D.; Stables, Simon; Tse, Rexson
Abstract : Abstract: Cerebrospinal fluid (CSF) is often analyzed at postmortem. The presented preliminary study compared postmortem CSF samples for biochemical analysis from the subarachnoid space around the spinal cord and ventricular space of the brain. This study compared 15 paired CSF samples in which the CSF from the subarachnoid space via lumbar puncture had higher sodium and chloride levels and lower magnesium and potassium levels than CSF from the ventricles. The differences correlated significantly with the deceased's age and had a similar trend with postmortem interval. This study suggests that CSF from different collection sites has different electrolyte concentrations, which are age and possibly postmortem interval dependent. When collecting CSF, the pathologist should document the collection site, age, and postmortem interval, and the mixing of CSF samples from different sites should be avoided. Further studies are warranted to clarify other possible reasons to explain the observed differences.